IMPLEMENTASI DETEKSI DINI MINAT BAKAT BAGI PENYANDANG DISABILITAS - Ajeng Intan Nur Rahmawati; Leny Latifah; Moh Ahsan (GANESHA: Jurnal Pengabdian Masyarakat, 2025)
Early Detection of Interests and Talents Assisted by 3D Interactive Modules for Disabled Facilitators in Improving Career Decision-Making Services is a community service activity funded by the Directorate of Research, Technology, and Community Service (DRTPM), Directorate General of Higher Education, Research, and Technology, Ministry of Education, Culture, Research, and Technology. The purpose of this activity is to provide training to people with disabilities so that they can conduct early detection of interests and talents using 3D interactive modules. Early detection of interests and talents is an important step in helping people with disabilities make more appropriate career decisions. The results of this community service activity are expected to be able to improve the quality of facilitator services in assisting people with disabilities in the career decision-making process. With better early detection of interests and talents, people with disabilities will have wider access to information about career potential that suits their interests and abilities. In addition, the 3D interactive technology applied in this module is also expected to be a model for the development of similar training methods in the future.